The Neglected Virome of Triatomine Insects - Cardoso, Maira Arruda; Brito, Tarcísio Fontenele de; Brito, Ingrid Alexandre de Abreu; Berni, Mateus Antonio; Coelho, Vitor Lima; Pane, Attilio (Frontiers in Tropical Diseases, 2022)
The Triatominae subfamily (Reduviidae) harbors some hematophagous insect species that have been firmly connected to the transmission of Trypanosoma cruzi, the causative agent of Chagas disease. Triatomines not only host and transmit trypanosomatids, but also coexist with a variety of symbiotic microorganisms that generally reside in the insect’s intestinal flora. The microbiome has profound effects on the physiology, immunity, fitness and survival of animals and plants. The interaction between triatomines and bacteria has been investigated to some extent and has revealed important bacteria symbionts. In contrast, the range of viral species that can infect triatomine insects is almost completely unknown. In some cases, genomic and metatranscriptomic approaches have uncovered sequences related to possible viral genomes, but, to date, only eight positive single-strand RNA viruses, namely Triatoma virus and Rhodnius prolixus viruses 1 - 7 have been investigated in more detail. Here, we review the literature available on triatomine viruses and the viruses-insect host relationship. The lack of broader metagenomic and metatranscriptomic studies in these medically relevant insects underscores the importance of expanding our knowledge of the triatomine virome both for surveillance purposes as well as to possibly harness their potential for insect vector population control strategies.